2001
DOI: 10.1292/jvms.63.591
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Manipulations of the Extinction Process of Fear-Induced Ultrasonic Vocalization in Rats.

Abstract: The effects of pharmacological manipulation on the extinction process of fear-induced ultrasonic vocalizations (USVs), which are considered distress calls related to anxiety, were investigated. Male Wistar rats were conditioned to emit USVs by being given repeated electrical foot-shocks while in a chamber. After 10 sessions of conditioning, the animals started to emit USVs upon mere exposure to the shock chamber without being shocked. Using these animals, the extinction process of the USVs was examined. With r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 44 publications
(73 reference statements)
3
7
0
Order By: Relevance
“…Diazepam was included in the design to compare with the acquisition experiments. Further, while there are studies on the effects of diazepam on the extinction of conditioned contextual fear responses, 27,28 there are few data on its effects on extinction of a cue-induced conditioned fear response. After 30 min, the rats were put in the conditioning box, and the conditioned stimulus light was presented 30 times with an interstimulus interval of 1 min (extinction training 29 ).…”
Section: Extinction Of Fpsmentioning
confidence: 99%
“…Diazepam was included in the design to compare with the acquisition experiments. Further, while there are studies on the effects of diazepam on the extinction of conditioned contextual fear responses, 27,28 there are few data on its effects on extinction of a cue-induced conditioned fear response. After 30 min, the rats were put in the conditioning box, and the conditioned stimulus light was presented 30 times with an interstimulus interval of 1 min (extinction training 29 ).…”
Section: Extinction Of Fpsmentioning
confidence: 99%
“…The rat social interaction test is a widely used assay that assesses the time two unfamiliar rats spend actively interacting in a novel aversive environment; compounds that have anxiolytic properties increase that time (File and Seth, 2003). Moreover, ultrasonic (22 kHz) vocalization in rats seems to reflect their emotional state and drug-induced reduction of ultrasonic vocalization induced by an aversive stimulus is used as an index of anxiolytic activity (Kikusui et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of diazepam withdrawal on ultrasound emissions in rodents were previously demonstrated in some studies that used acoustic stimuli and foot-shocks as ultrasound-elicited stimuli, mainly using the subcutaneous or intraperitoneal injections as the method of drug delivery (Kikusui et al, 2001;Miczek and Vivian, 1993;Nielsen and Sanchez, 1995;Vivian et al, 1994). As it was observed that the chronic intraperitoneal injection of a placebo solution elicits, by itself, anxiety in rats tested in the EPM (Griebel et al, 1994), in this study we used the voluntary oral intake as the method of choice.…”
Section: Discussionmentioning
confidence: 94%